Manajemen Strategi dalam Bisnis Syariah untuk Keberlanjutan dan Keunggulan Kompetitif - Siti Hanifah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
With increasing global competition and rapid technological advancements, sharia businesses face the challenge of achieving sustainability while maintaining a competitive advantage in accordance with Islamic principles. This study aims to examine how the application of strategic management in sharia businesses can support sustainability and market differentiation based on ethical values. The research method used in this study is a literature review, analyzing various academic sources related to business strategy, sustainability, and Islamic economic principles. The findings indicate that effective strategic management, when properly implemented through the processes of formulation, execution, and evaluation, can help business practitioners adapt to changes in both the internal and external environments. In sharia businesses, strategies should be rooted in values such as honesty, trustworthiness, and social responsibility. These values not only serve as moral guidelines but can also enhance customer loyalty and provide a competitive edge. Furthermore, the adoption of digital technology and promotional strategies aligned with Islamic values has been shown to broaden market reach and improve operational efficiency. SWOT analysis is also employed as a tool to inform relevant and strategic decision-making. Therefore, the application of strategic management in accordance with Islamic values can effectively create businesses that are not only competitive but also sustainable and beneficial to society.